(untitled) (Journal of economic and management development research, 2026)
This paper provides a comprehensive discussion of the digital economy. It first points out that the digital economy has penetrated every aspect of daily life and has become a common way of living. It then explains the definition of the digital economy, including such core components as digital industrialization and industrial digitalization, as well as important dimensions such as digital governance and data valorization. The paper further shows that China’s digital economy has developed rapidly, featuring a large scale and fast growth rate, while reshaping the economic structure and exhibiting distinctive regional distribution characteristics. It also introduces the core technologies and applications of the digital economy, such as big data and cloud computing. In addition, the paper analyzes how the digital economy has transformed lifestyles in areas such as shopping and travel, while also bringing new opportunities for entrepreneurship and innovation, as well as new challenges such as the digital divide. Finally, it looks ahead to the future development of the digital economy, noting trends such as the comprehensive empowerment of artificial intelligence, and calls on people to embrace the digital era and jointly create a better future.